(untitled) (Journal of Science and Technology, 2016)
This paper took an in-depth look at key words and synonymous concepts such as libraries, knowledge and information. Thereafter the prowess of the library in all ramifications as an engine for the acquisition of knowledge and dissemination of information was copiously examined. This was done against the background of Information Communication Technology (ICT), which has undoubtedly launched the world into a new era (New World Order) reminiscence of the Industrial Revolution. The dynamism of the library in this new world can therefore be expressed in continuous learning. This paper sees the library as the logical and convenient locale for it. The paper concluded by recommending the library as a home for all and sundry information seekers - the academically famished university lecturer, the diplomat, the industrialist and the young at heart. The library indeed, as concluded in this paper should be our companion from cradle to grave.